2021
DOI: 10.1155/2021/6650464
|View full text |Cite
|
Sign up to set email alerts
|

The Secretome Deregulations in a Rat Model of Endotoxemic Shock

Abstract: Introduction. Septic shock is a systemic inflammatory response syndrome associated with organ failures. Earlier clinical diagnosis would be of benefit to a decrease in the mortality rate. However, there is currently a lack of predictive biomarkers. The secretome is the set of proteins secreted by a cell, tissue, or organism at a given time and under certain conditions. The plasma secretome is easily accessible from biological fluids and represents a good opportunity to discover new biomarkers that can be studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Molecules with anti-inflammatory properties have been found in omega-3 fatty acids eicosapentaenoic acid, docosahexaenoic acid, and arachidonic acid ( 49 ). A study also showed that oxidative stress and lipid metabolism promote sepsis development ( 50 ). Furthermore, other pathways, including urea cycle metabolism, glutathione metabolism, and primary bile acid biosynthesis, were also affected in the MTS group.…”
Section: Discussionmentioning
confidence: 99%
“…Molecules with anti-inflammatory properties have been found in omega-3 fatty acids eicosapentaenoic acid, docosahexaenoic acid, and arachidonic acid ( 49 ). A study also showed that oxidative stress and lipid metabolism promote sepsis development ( 50 ). Furthermore, other pathways, including urea cycle metabolism, glutathione metabolism, and primary bile acid biosynthesis, were also affected in the MTS group.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma secretome is easily accessible by a non-invasive approach and can be analyzed by non-targeted mass spectrometry [ 11 ]. Recently, a study identified, through the investigation of the secretome of a rat model in endotoxemic shock, deregulated proteins throughout the course of the pathology [ 101 ]. The analysis of the secretome of horses in sepsis could be a source of diagnostic, prognostic biomarkers, and therapeutic targets.…”
Section: Main Biomarkers Of Equine Sepsis: a Proof Of Concept For Hum...mentioning
confidence: 99%